THE IMPACT OF HUMAN CAPITAL DEVELOPMENT ON POVERTY RATE IN PURWOREJO REGENCY - Basworo, Fajar Hanung; Dwi Atmanti, Hastarini (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the impact of human capital development on poverty levels in Purworejo Regency during the 2019-2023 period. The main focus is to identify variables related to poverty and provide human capital-based policy recommendations. This research uses econometric models, namely the Ordinary Least Square (OLS) and Seemingly Unrelated Regression (SUR) models. The dependent variable analyzed is the poverty rate, while the independent variables include Mean Years of Schooling (MYS), Expected Years of Schooling (EYS), Life Expectancy Rate (LER), and Per Capita Expenditure (PCE). The findings reveal significant correlations between all human capital variables and poverty reduction. The health dimension, measured by LER, showed the strongest impact on poverty reduction. The SUR model shows a 4.01% improvement in efficiency compared to the OLS model. Poverty alleviation policies should focus on strengthening the healthcare system, improving educational access, and empowering the economy, with direct interventions in healthcare and education. This study stands out for its use of the SUR model to analyze the simultaneous effects of human capital variables on poverty, addressing the limitations of previous studies that used the OLS model.